An Evaluation of Marriage Dowry Using Digital Money from the Perspective of the Four Madhhabs - Wijaya, Abdi; Riskah (Parewa Saraq: Journal of Islamic Law and Fatwa Review, 2022)
This study aims to determine the position of the four madhhabs and understand their point regarding giving dowry using digital money. The library study method was adopted with a comparative approach. Based on the arguments mentioned by the al-Shafi’i madhhab, giving a dowry using digital money can be used or valid, inasmuch as the contract is in accordance with existing provisions. Therefore, the provision of dowry using digital money is still an agreement between the parties concerned. In this contemporary era, everything will shift to the world of technology or digital, and all possibilities will occur, including the transformation of purchasing and selling tools into digital money. The madhhab priest explains that it is permissible and legal, insofar as it does not deprive him of the rights and obligations in the dowry.